Preparation of Activated Carbon From Kluwek (Pangium Edule) Shells as An Adsorbent for Effective Removal of Free Fatty Acid (FFA) from used cooking oil - Efrillia, Fananda Sherly; Fajar, Mutiara (Green and Sustainable Materials Society, 2025)
Used cooking oil from repeated use exhibits characteristics such as high free fatty acid (FFA) content, brownish color, and rancid odor, which pose risks to both health and the environment. This study aims to analyze the effectiveness of activated carbon derived from Pangium edule shells in adsorbing FFAs, color, and odor from oil samples, as well as to identify the functional groups present in the adsorbent using FTIR analysis. The adsorption process was conducted with varying adsorbent masses (5, 10, and 15 grams) and contact times (60, 90, and 120 minutes) to determine the optimal removal conditions. The results indicate that NaOH-activated Pangium edule shell carbon contains hydroxyl (-OH) and carbonyl (C=O) functional groups, which play a crucial role in adsorption. After the adsorption process, an efficiency of 85.57% was achieved, reducing the FFA content from 1.88% to 0.27% under optimal conditions (adsorbent mass of 15 grams and contact time of 120 minutes), along with a significant color change. The shift in FTIR spectrum intensity after adsorption suggests that polar compounds such as FFAs interacted with active sites on the adsorbent surface. Thus, activated carbon from Pangium edule shells is effective for treating used cooking oil in an environmentally friendly manner, meeting the quality standards of SNI 7709:2019.